2016
DOI: 10.1021/acs.biochem.5b01307
|View full text |Cite
|
Sign up to set email alerts
|

The Transmembrane Domain of HIV-1 gp41 Inhibits T-Cell Activation by Targeting Multiple T-Cell Receptor Complex Components through Its GxxxG Motif

Abstract: To successfully infect and persist within its host, HIV-1 utilizes several immunosuppressive motifs within its gp41 envelope glycoprotein to manipulate and evade the immune system. The transmembrane domain (TMD) of gp41 downregulates T-cell receptor (TCR) signaling through a hitherto unknown mechanism. Interactions between TMDs within the membrane milieu have been shown to be typically mediated by particular amino acids, such as interactions between basic and acidic residues and dimerization motifs as GxxxG. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 53 publications
(96 reference statements)
3
25
0
Order By: Relevance
“…In vitro infectivity and cell–cell fusion do not, however, mimic all the conditions under which the virus moves from one cell to another in an infected individual, nor are those assays particularly sensitive to physiologically relevant kinetic parameters. We note that R696 occupies a ‘d’ position in the coiled coil, with its C β facing inwards toward the trimer interface, unlike its configuration in previously proposed models . Its interactions in the trimeric coiled coil are probably those of optimal stability, once having paid the energetic cost of burying its charge.…”
Section: Structure Of the Transmembrane Domain Of Hiv‐1 Envmentioning
confidence: 70%
“…In vitro infectivity and cell–cell fusion do not, however, mimic all the conditions under which the virus moves from one cell to another in an infected individual, nor are those assays particularly sensitive to physiologically relevant kinetic parameters. We note that R696 occupies a ‘d’ position in the coiled coil, with its C β facing inwards toward the trimer interface, unlike its configuration in previously proposed models . Its interactions in the trimeric coiled coil are probably those of optimal stability, once having paid the energetic cost of burying its charge.…”
Section: Structure Of the Transmembrane Domain Of Hiv‐1 Envmentioning
confidence: 70%
“…Mutagenesis studies showed that the transmembrane domain (TMD) of gp41 is not merely a membrane anchor, but plays critical roles in membrane fusion and viral infectivity 16–20 . Moreover, recent studies showed that truncations in the cytoplasmic tail of gp41 could alter the antigenic surface of the Env ECD on the opposite side of the membrane 21 , suggesting that the ECD, the TMD, and the membrane proximal regions are conformationally coupled, and thus the conformational stability of the TMD is an important consideration for immunogen design in B-cell based HIV-1 vaccine development.…”
mentioning
confidence: 99%
“…Due to the unusual position of the R696, the membrane partition of the gp41 TMD has been controversial 20, 22, 2627 . Our solvent PRE analysis now confirms that R696 resides in the middle of the membrane (Fig.…”
mentioning
confidence: 99%
“…It was previously shown that hydrophobic peptides conjugated to lysine tags were correctly oligomerized and inserted into the membrane (35,36). For assays with fluorescent peptides, the addition of rhodamine 5(6)-carboxytetramethylrhodamine N-succinimidyl ester (TAMRA, BioChemika) or NBD-F (2-fold excess) fluorescent probe to the N terminus of the peptides was performed by standard Fmoc chemistry (37).…”
Section: Peptide Synthesis Purification and Fluorescent Labelingmentioning
confidence: 99%